Race and radicalism in the Union Army - Lause, Mark A. (University of Illinois Press, 2009)
In this portrait of interracial activism, Mark A. Lause documents the efforts of radical followers of John Brown to construct a triracial portion of the Federal Army of the Frontier. Mobilized and inspired by the idea of a Union that would benefit all, black, Indian, and white soldiers fought side by side, achieving remarkable successes in the field. Against a backdrop of idealism, racism, greed, and the agonies and deprivations of combat, Lause examines links between radicalism and reform, on the one hand, and racialized interactions among blacks, Indians, and whites, on the other. --From publisher's description.